Efficacy and safety of Iguratimod as an add-on therapy for refractory lupus nephritis: A preliminary investigational study - Yan, Qingran; Zhang, Mei; Du, Fang; Kang, Yuening; Ye, Ping; Li, Qianqian; Liu, Bei; Dai, Min; Bao, Chunde (Frontiers in Immunology, 2023)
Abstract Objectives: IGU (IGU), a novel immunomodulatory agent for rheumatoid arthritis, has been shown to be effective and safe as monotherapy in a small population with refractory lupus nephritis (LN). The aim of this prospective study was to evaluate the efficacy and safety of IGU as an add-on therapy in patients with refractory LN in the context of clinical practice. Methods: We have enrolled LN patients since 2019 at Renji Hospital. All participants should have recurrent or refractory LN with at least one immunosuppressant (IS) and have a baseline urine protein/creatinine ratio (UPCR) >1.0. After enrollment, we added IGU (25 mg twice daily) to one of their previous immunosuppressants (IS) without increasing the dose of steroids. The primary outcome was the complete renal response (CRR) in the 6th month. UPCR decrease of over 50% was defined as partial response (PR). Extended follow-up was performed after the initial 6 months. Results: We enrolled 26 eligible participants. 11/26 patients had chronic kidney disease (CKD) stage 2/3 at the baseline. The IS combined with IGU included mycophenolate mofetil, tacrolimus, and cyclosporin A. No IS change was allowed. 80.7% of patients had baseline steroids less than 0.5mg/kg daily and there was no steroids escalation during the IGU treatment. The CRR rate was 42.3% (11/26) at month 6. With a median follow-up of 52 weeks (range: 23-116 weeks), the CRR rate at the last visit was 50% (13/26) and 73.1% (19/26) of patients had UPCR decrease of over 50%. Six patients withdrew, three for no response and three for renal flare after initial CRR. One patient had an estimated glomerular filtration rate worsening of over 20% and was classified as renal flare. Three mild to moderate adverse events were recorded. Conclusions: Our investigation merits further investigation in IGU as a potentially tolerable component of combination therapy for refractory LN.